Impact of COVID-19 pandemic on the PREDIMED-Plus randomized clinical trial: Effects on the interventions, participants follow-up, and adiposity - Paz-Graniel, Indira; Fitó, Montserrat; Ros, Emilio; Buil-Cosiales, Pilar; Corella, Dolores; Babio, Nancy; Martínez, J. Alfredo; Alonso-Gómez, Ángel M.; Wärnberg, Julia; Vioque, Jesús; Romaguera, Dora; López-Miranda, José; et al. (Frontiers in Nutrition, 2023)
Background: The COVID-19 pandemic has affected the implementation of most ongoing clinical trials worldwide. We aimed to report the effects of the pandemic on the deliverance of interventions in PREDIMED-Plus, a multicenter trial of diet and lifestyle, aimed at weight-loss and cardiovascular disease prevention; to describe strategies established to mitigate adverse effects of lockdown on data collection and adiposity. Methods: We assessed the integrity of the PREDIMED-Plus trial during 5 identified periods of the COVID-19 pandemic determined according to restrictions dictated by the Spanish government authorities. A standardized questionnaire was delivered to each of the 23 PREDIMED-Plus recruiting centers to collected data regarding the trial integrity. The effect of the restrictions on intervention components (diet, physical activity) was evaluated with data obtained in the three identified lockdown phases: pre lockdown, lockdown proper, and post lockdown. Results: During the lockdown (March/2020-June/2021), 4,612 participants (48% women, mean age 65y) attended pre-specified yearly follow-up visits to receive lifestyle recommendations and obtain adiposity measures. The overall mean(SD) of the proportions reported by each center showed that 40.4%(25.4) participants had face-to-face interviews. 39.8%(18.2) participants were also contacted by telephone and 35%(26.3) by electronic means. Participants' follow-up and data collection rates increased across lockdown periods (from ≈10% at onset to ≈80% at the end). Compared to pre-lockdown, waist circumference increased during (0.75cm [95%CI: 0.60 to 0.91]) and after (0.72cm [95%CI: 0.56 to 0.89]) lockdown. Body weight did not change during lockdown (0.01kg [95%CI: -0.10 to 0.13) and decreased after lockdown (-0.17kg [95%CI: -0.30 to -0.04]). Conclusions: Mitigating strategies to enforce the intervention and patient's follow-up during lockdown have been successful in preserving the integrity of the trial and ensuring its continuation, with minor effects on adiposity. Trial registration: ISRCTN89898870. Retrospectively registered on 24 July 2014